PENERAPAN KOMPETENSI KEPRIBADIAN GURU PAI - Najamuddin Petta Solong; Luki Husin (Universitas Islam Sultan Agung, 2020)
This study aims to analyze the application of the personal competence of Islamic education teachers in Madrasah Aliyah Muhammadiyah Kota Gorontalo shown in three domains of personality competence consisting of three competency aspects, namely: acting in accordance with religious, legal, social, and national cultural norms; show an adult and exemplary person; and work ethic, sense of responsibility and pride in being a teacher. Research on this is reinforced by the results of teacher performance assessments on teacher personality competencies by the principal according to the data obtained in the field. PAI teachers, for example, do not share their experiences with colleagues, including inviting them to observe their teaching methods and provide input, show less good behavior that image madrasah's good name, rarely ask permission and inform earlier, by providing valid reasons and evidence for not attending activities has been planned, completes all administrative and non-learning tasks in a timely manner according to the set standards, contributes less to the development of madrasas and lacks achievements that have a positive impact on the reputation of madrasahs. Keywords: Personal Competence, Islamic Education Teacher